Antioxidant enzyme peroxiredoxin 5 regulates cyst growth and ciliogenesis via modulating Plk1 stability. Issue 1 (9th December 2021) - Agborbesong, Ewud; Zhou, Julie Xia; Li, Linda Xiaoyan; Calvet, James P.; Li, Xiaogang
Abstract: Oxidative stress is emerging as a contributing factor to the homeostasis in cystic diseases. However, the role antioxidant enzymes play in the pathogenesis of autosomal dominant polycystic kidney disease (ADPKD) remains elusive. Peroxiredoxin 5 (Prdx5) is an antioxidant enzyme that catalyzes the reduction of H2 O2 and alkyl hydroperoxide and plays an important role in different biological processes. In this study, we show that Prdx5 is downregulated in a PKD mutant mouse model and ADPKD patient kidneys. Knockdown of Prdx5 resulted in the formation of cysts in a three‐dimensional mouse inner medullar collecting duct (IMCD) cell Matrigel culture system. The mechanisms of Prdx5 deficiency mediated cyst growth include: (1) induction of oxidative stress as indicated by increased mRNA expression of heme oxygenase‐1, an oxidant stress marker; (2) activation of Erk, S6 and mTORC1, which contribute to cystic renal epithelial cell proliferation and cyst growth; (3) abnormal centrosome amplification and multipolar spindle formation which result in genome instability; (4) upregulation of Polo‐like kinase 1 (Plk1) and Aurora kinase A, important mitotic kinases involved in cell proliferation and ciliogenesis; (5) impaired formation of primary cilia in mouse IMCD3 and retinal pigment epithelial cells, which could be rescued by inhibiting Plk1 activity; and (6) restraining the effect of Wnt3a and Wnt5a ligands on primary cilia in mouse IMCD3 cells, while regulating the activity of the canonical and non‐canonical Wnt signaling in a separate cilia independent mechanism, respectively. Importantly, we found that targeting Plk1 with its inhibitor, volasertib, delayed cyst growth in Pkd1 conditional knockout mouse kidneys. Together, these findings indicate that Prdx5 is an important antioxidant that regulates cyst growth via diverse mechanisms, in particular, the Prdx5‐Plk1 axis, and that induction and activation of Prdx5, alone or together with inhibition of Plk1, represent a promising strategy for combatting ADPKD.